2021
DOI: 10.1136/heartjnl-2020-318062
|View full text |Cite
|
Sign up to set email alerts
|

Remote monitoring in heart failure: current and emerging technologies in the context of the pandemic

Abstract: The incidence of heart failure (HF) remains high and patients with HF are at risk for frequent hospitalisations. Remote monitoring technologies may provide early indications of HF decompensation and potentially allow for optimisation of therapy to prevent HF hospitalisations. The need for reliable remote monitoring technology has never been greater as the COVID-19 pandemic has led to the rapid expansion of a new mode of healthcare delivery: the virtual visit. With the convergence of remote monitoring technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…Remote home monitoring services have previously been implemented in the UK for chronic conditions 2,3 , and during the first wave of the pandemic these services were set-up and piloted for COVID-19 patients in England 4 . These services were subsequently rolled out nationally, known as ‘COVID Oximetry at home (CO@h)’ or ‘Virtual Wards’ for COVID-19 patients who had been discharged early from hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Remote home monitoring services have previously been implemented in the UK for chronic conditions 2,3 , and during the first wave of the pandemic these services were set-up and piloted for COVID-19 patients in England 4 . These services were subsequently rolled out nationally, known as ‘COVID Oximetry at home (CO@h)’ or ‘Virtual Wards’ for COVID-19 patients who had been discharged early from hospital.…”
Section: Introductionmentioning
confidence: 99%
“…RPM engages patients as equal partners in their care and should therefore theoretically appeal to care providers and to patients with HF. 31 …”
Section: Innovation Through Covid-19mentioning
confidence: 99%
“…In the SUPPORT HF trial, the digital home monitoring with centralized specialists showed positive results in terms of efficacy, but no improvements in the use of evidence-based treatments have been found in digital home monitoring alone [68]. Favorable results come from a selected group of patients with HF (New York Heart Association [NYHA] class II-III, LVEF <45% or-if higher than 45%-in therapy with oral diuretics) who have been randomized to a web-based system plus usual care or to usual care only [69]. The CHAMPION-HF trial shows an adequate adjustment of the medical therapy and a reduction in HF hospitalizations using the CardioMEMS monitor (a real time sensor of pulmonary pressure percutaneously implanted in the pulmonary artery) [70].…”
Section: The Importance Of Telemedicine In the 21st Century And The Covid Eramentioning
confidence: 99%